Spontaneous rupture of extensor pollicis longus after distal radius fracture: a case report - Jiménez-Yarza, Miguel; Téllez-Pallares, Fernando; Olvera-Yarza, Francisco Alberto; Solano-Vázquez, José Gerardo (International Journal of Research in Medical Sciences, 2024)
Extensor pollicis longus tendon rupture, rare and linked to trauma or arthritis, is prevalent post-distal radius fractures. Mechanisms include friction and vascular issues. Manifestations occur 4-8 weeks’ post-trauma. We present the case of A 31-year-old male, post-motorcycle accident surgery for distal radius fracture, faced extensor pollicis longus tendon rupture. A surgical intervention transposed the extensor indicis proprius tendon, restoring thumb function. Successful closure and splinting showed no movement limitations at the 12-week follow-up, prompting a rehabilitation referral. Distal radius fracture treatments, whether operative or non-operative, entail risks of extensor tendon complications, notably extensor pollicis longus. While direct suture repair is optimal, studies endorse effective restoration of thumb function through tendon grafts, particularly utilizing the extensor indicis proprius. Rupture of the extensor pollicis longus, while uncommon, often occurs with distal radius fractures. Extensor indicis proprius grafting is recommended for superior efficacy over alternatives, emphasizing the need for accurate and timely diagnosis.